ANALISIS PENGARUH CORPORATE GOVERNANCE, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI periode 2014-2018) - Saraswati, Inez Yustika; Kholiq Mahfud, Mohammad (Faculty of Economics and Business Diponegoro University, 2020)
Earning management is a management action to manage the profitability of a company. This study aims to examine the effect of corporate governance, leverage and firm size on the earning management practices. Corporate governance performed by independent commissioners proportion, audit committee, and managerial ownership. The dependent variable, earnings management, is measured by the discretionary accrual. This study uses secondary data were taken from the manufacturing companies which are listed in Indonesian Stock Exchange. 37 manufacturing companies selected as study samples on the period of 2014 until 2018 based on purposive sampling method. The analytical method for this study uses multiple linear regression using the classical assumption test and regression analysis with a significance level of 5%. Based on the results of research that simultaneously uses the F test variable independent commissioners proportion, audit committee, managerial ownership, leverage, and firm size significantly influence the earning management. The result of partial testing using the T test show that independent commissioners proportion, audit committee, managerial ownership, leverage, and firm size have a negative and significant effect on earning management.